Effect of ramadan fasting on breast milk - AKTAÇ, ŞULE; KUNDAKÇI, SİMAY (My University, 2023)
Introduction: Breast milk is an excellent biofluid that ensures optimal growth, development, and strong immunity of the baby. Breast milk content may alter depending on duration and time of breastfeeding, the infant\"s age, and maternal health status. There are few studies in the literature investigating the effect of religious fasting on breast milk composition. Method: The study included 21 fasting and 27 nonfasting mothers who exclusively breastfed their babies in 2021 Ramadan month. The energy, carbohydrate, protein, and lipid levels of the collected breast milk samples and the macro- and micronutrient contents of the mothers\" diets and the weight gain of the infants during the study were evaluated. Results: The mothers\" ages, education levels, and weights at birth and at the time of sampling were similar. There was no significant difference between the energy, carbohydrate, protein, and lipid composition of breast milk in fasting and nonfasting mothers. Although daily energy, protein, carbohydrate, fiber, and vitamin intakes between two groups were similar, mean daily intake of lipid, sodium, chloride, iodine, and omega-3 fatty acids was determined significantly higher in study group. Also, there was no difference in the weight gain of babies during the month of Ramadan. Conclusion: Religious fasting of mothers does not affect the energy and macronutrient content of breast milk. In addition, fasting does not seem to affect the weight of mothers and babies.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Hemşirelik; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Child Health and Diseases; Surgery Medicine Sciences; Obstetrics and Gynecology; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; HEMŞİRELİK; KADIN HASTALIKLARI & DOĞUM; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; NURSING; OBSTETRICS & GYNECOLOGY; PEDIATRICS; Pediatri; Sağlık Politikaları; Doğum ve Jinekoloji; Annelik ve Ebelik; Pediatrics; Health Policy; Maternity and Midwifery; breast milk; breastfeeding; fasting; Ramadan